Novel control designs for domino wireless power transfer systems - Chay, Leonard Hao En (Nanyang Technological University, 2024)
This study investigates Domino Wireless Power Transfer (WPT) systems, analysing and optimising them. The primary objective is to develop novel control algorithms to enhance energy efficiency and deliver fixed voltage (CV) and current (CC) outputs, regardless of the load. The study involves the examination of theoretical concepts, developing dynamic models for high-order power electronics, and validating control systems through simulation using MATLAB/Simulink. This study investigates the impact of different loads on the performance of a system, with a particular focus on open-loop control approaches. This study focuses on the difficulties related to fluctuations in load with Domino WPT technology. The efficacy of the suggested control algorithms under various load situations is assessed through the implementation of simulations. This study provides valuable insights into the flexibility and resilience of Domino WPT systems. On the whole, this study provides a significant contribution towards the advancement of wireless power transmission technology. Additionally, Domino WPT systems have significant avenues for improving energy efficiency and guaranteeing secure and dependable electricity transmission